PKM Peraturan dan Teknik Dasar Sepakbola - Muhammad Nur; Yasriuddin Yasriuddin; Andi Masjaya AM; Ilham Kamaruddin (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The problem with this community service is that knowledge and understanding of the basic rules and techniques of football are not yet known by the students of SD Inpres Perumnas Antang III Makassar City. The purpose of this service is to increase partner knowledge about the rules of the game and basic football techniques for students of SD Inpres Perumnas Antang III Makassar City in playing football with the hope of increasing the quality of playing football for students of SD Inpres Prumnas Antang III Makassar City, Makassar. The community partnership program activities are divided into two activities, namely: (1) The theoretical explanation activity is carried out for one day, namely explaining the basic rules and techniques of football. (2) Practical activities, carried out for 6 days to directly practice the basic techniques of playing football. The results of community service show that partners who take part in this PKM are able to understand the basic rules and techniques of football and are able to practice them well. The conclusion of this PKM is that there is an increase in participants' knowledge about the rules of the game and participants' skills on how to play football according to the correct basic technique.